Samoopredelitev odraslih oseb z diagnozo avtizem iz Slovenije - Žumbar, Tina (Sodobna pedagogika, 2024)
Naming an individual or a minority group is a very sensitive issue. In most societies that follow the principles of respect and non-discrimination, this issue is paid considerable attention in research. The language we use to describe minority groups can define their positions vis-a-vis the majority and establish a social hierarchy, as can the perspectives through which the defining characteristics of a particular group are viewed (e.g., language, nationality, gender and special needs). Characteristics that also have a significant impact on the lives of minority group members are often overlooked. In recent years, it has become commonplace to include the views of the members of the minority group under study concerning their language preferences. This aspect has been the main topic of our research, part of which is presented in this article. In our study, adults diagnosed with autism (n = 55) explained which terms used to refer to them in Slovenia they find offensive and which ones they prefer. The qualitative analysis found no consensus among the participants regarding preferred terms. Concerning the two main paradigms described in the article (person-first language and identity-first language), there was a predilection for person-first terminology. The participants identified the term person with autistic disorders as the least desirable, even though this is currently the official wording adopted in Slovenian legislation, mainly because it emphasises pathology and points to a flaw in the person.
Keywords: autism; Avtizem; identity-first language; language preferences; najprej identiteta; najprej oseba; Odrasli; person-first language; samoopredelitev; terminologija; terminology